Beyond utility and enjoyment : the impact of environmental value on continuance intention of theme park apps - Long, Ting; Suomi, Reima (Springer Nature, 2026)
Theme park apps have emerged as digital solutions to address environmental issues within parks. Yet, few studies have explored their influence on user satisfaction and continuance intention from an individual user’s perspective. This study investigates the motivators of satisfaction and continuance intention for a theme park app through the lens of perceived value. Specifically, it posits that environmental value (operationalized as perceived environmental friendliness), along with the traditionally studied functional (measured by perceived usefulness), hedonic (captured by perceived enjoyment), and social values (reflected by perceived social interaction), jointly shape user satisfaction and continuance intention. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method was applied to analyse survey data collected from users in China and Europe (N = 646). The results indicate that perceived environmental friendliness significantly influences continuance intention but has no significant effect on satisfaction. Perceived usefulness and enjoyment positively impact both satisfaction and continuance intention, while perceived social interaction does not significantly affect either. By incorporating environmental value into the perceived value framework, this study provides a more comprehensive understanding of the factors driving satisfaction and continuance intention in theme park app usage.